A multivariable multiobjective predictive controller - Aicha, Faten Ben; Bouani, Faouzi; Ksouri, Mekki (Zielona Góra: Uniwersytet Zielonogórski)
Predictive control of MIMO processes is a challenging problem which requires the specification of a large number of tuning parameters (the prediction horizon, the control horizon and the cost weighting factor). In this context, the present paper compares two strategies to design a supervisor of the Multivariable Generalized Predictive Controller (MGPC), based on multiobjective optimization. Thus, the purpose of this work is the automatic adjustment of the MGPC synthesis by simultaneously minimizing a set of closed loop performances (the overshoot and the settling time for each output of the MIMO system).
Keywords: closed loop performance; coupled multivariable system; generalized predictive control; multiobjective optimization; weighted sum method; NSGA-II